LISTENING ANXIETY AND LISTENING COMPREHENSION PERFORMANCE ACROSS DIFFERENT GENDER AMONG THE FIRST YEAR STUDENTS OF VOCATIONAL HIGH SCHOOL - dwi liyandari (Language-Edu, 2020)
Dwi LiyandariEnglish Language Teaching Study ProgramPostgraduate School, Universitas Islam Malang, IndonesiaEmail: dwimirzaukail@gmail.com AbstractThis study aimed to investigate the correlations among anxiety, listening performance and gender in Vocational High School. The data was taken from the first year students of SMKN 1 Panggungrejo by using Foreign Language Listening Anxiety Questionnaire (FLLAQ) that consisted of 33 five-Likert items. These FLLAQ were administered to 76 students of the first years of SMKN 1 Panggungrejo Blitar, Institution Financial and Accounting Department and Light Vehicle Engineering Department. The result of this study was there ere 51% of the students who had undergone the listening anxiety while listening to English. It is 39 students. The questionnaire consisted of 33 items so the score ranging from 33 to 165. So, 38 students felt their listening anxiety and the rest, 38 students,  felt low listening anxiety. From the statistic description of anxiety in listening and the test result of students’ listening comprehension can be deduced that if the students’ listening anxiety is higher, the students’ listening comprehension achievement is also getting higher. There was low correlation between listening anxiety of students with  their listening comprehension performance. It is noted that between gender and students’ listening anxiety, there was no significant correlation between. A significant correlation can be stated between students’ gender and listening performance. Keywords: anxiety, gender, listening comprehension.